Sistem Monitoring pH Air pada Budidaya Lele Berbasis IoT - Ananta Saka Hutama; Dimas Febriawan (Jurnal Teknik Informatika dan Komputer, 2023)
Maintaining water quality is the most important thing in every aquaculture, in this case catfish farming, so in maintaining water quality, especially water pH, it is necessary to monitor the pH of water in fishery ponds. This activity aims to be able to create a tool. the firebase and blynk platforms use the node MCU microcontroller with the ESP-8266 module which can be monitored remotely in realtime 8266 with the method used is prototype, starting with identifying needs, designing, building and testing prototypes. The research process includes measuring the pH of pool water by a water pH meter sensor device and the data is forwarded and processed by the MCU node which already has an ESP-8266 (wifi module) which can send pH reading data via the internet to firebase and blynk's realtime database platform so that later with it's easy as long as you are in the same network, information on measurement results will be easily accessed via any device, be it a PC, laptop or smartphone. Based on the test result that this monitoring system can run well to measure the pH of water with a relative error of 0.581%. In the end the use of this tool is to benefit from the application and testing of the tool in this case it is expected that the pH quality of the catfish pond water is good.